Integral with Inverse Trigo

Calculus Level 4

i = 1 6 ( arcsin ( x i ) + arccos ( y i ) ) = 9 π \displaystyle \sum _{ i=1 }^{ 6 }{ \left( \arcsin ( { x }_{ i } ) +\arccos ( { y }_{ i } ) \right) } =9\pi

If the above equation satisfies, then find the value of

i = 1 6 x i i = 1 6 y i x ln ( 1 + x 2 ) ( e x 1 + e 2 x ) d x \displaystyle \int \limits_{ \displaystyle \sum _{ i=1 }^{ 6 }{ { x }_{ i } } }^{ \displaystyle \sum _{ i=1 }^{ 6 }{ { y }_{ i } } }{ x\ln { (1+{ x }^{ 2 }) } } \left( \frac { { e }^{ x } }{ 1+{ e }^{ 2x } } \right) \ \mathrm{d}x


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sandeep Bhardwaj
Sep 23, 2015

Since the range of arcsin ( x ) \arcsin(x) is [ π 2 , π 2 ] \left[ -\dfrac{\pi}{2}, \dfrac{\pi}{2} \right] and of arccos ( x ) \arccos(x) is [ 0 , π ] \left[ 0, \pi \right] .

Hence i = 1 6 ( arcsin ( x i ) + arccos ( y i ) ) = 9 π { \sum _{ i=1 }^{ 6 }{ \left( \arcsin ( { x }_{ i } ) +\arccos ( { y }_{ i } ) \right) } =9\pi} is satisfied only when { arcsin ( x 1 ) = arcsin ( x 2 ) = arcsin ( x 3 ) = arcsin ( x 4 ) = arcsin ( x 5 ) = arcsin ( x 6 ) = π 2 arccos ( y 1 ) = arccos ( y 2 ) = arccos ( y 3 ) = arccos ( y 4 ) = arccos ( y 5 ) = arccos ( y 6 ) = π \begin{cases} \arcsin(x_1)=\arcsin(x_2)=\arcsin(x_3)=\arcsin(x_4)=\arcsin(x_5)=\arcsin(x_6)=\dfrac{\pi}{2} \\ \arccos(y_1)=\arccos(y_2)=\arccos(y_3)=\arccos(y_4)=\arccos(y_5)=\arccos(y_6)=\pi \end{cases}

And to achieve the above situation, we have to conclude that { x 1 = x 2 = x 3 = x 4 = x 5 = x 6 = 1 y 1 = y 2 = y 3 = y 4 = y 5 = y 6 = 1 \begin{cases} x_1=x_2=x_3=x_4=x_5=x_6=1 \\ y_1=y_2=y_3=y_4=y_5=y_6=-1\end{cases}

Therefore we can evaluate i = 1 6 x i = 6 \displaystyle \sum _{ i=1 }^{ 6 }{ { x }_{ i } }=6 and i = 1 6 y i = 6 \displaystyle \sum _{ i=1 }^{ 6 }{ { y }_{ i } }=-6 . Therefore the given integral becomes 6 6 x ln ( 1 + x 2 ) ( e x 1 + e 2 x ) d x \displaystyle \int \limits_{ 6 }^{ -6 }{ x\ln { (1+{ x }^{ 2 }) } } \left( \frac { { e }^{ x } }{ 1+{ e }^{ 2x } } \right) \ \mathrm{d}x

And we know that [ x ln ( 1 + x 2 ) ( e x 1 + e 2 x ) ] \left[ { x\ln { (1+{ x }^{ 2 }) } } \left( \frac { { e }^{ x } }{ 1+{ e }^{ 2x } } \right) \right] is an odd function.

Hence using the property of the definite integrals that a a f ( x ) d x = 0 \displaystyle \int_{-a}^{a} f(x) dx=0 , if f ( x ) f(x) is an odd function, we can say that i = 1 6 x i i = 1 6 y i x ln ( 1 + x 2 ) ( e x 1 + e 2 x ) d x = 0 \displaystyle \int \limits_{ \displaystyle \sum _{ i=1 }^{ 6 }{ { x }_{ i } } }^{ \displaystyle \sum _{ i=1 }^{ 6 }{ { y }_{ i } } }{ x\ln { (1+{ x }^{ 2 }) } } \left( \frac { { e }^{ x } }{ 1+{ e }^{ 2x } } \right) \ \mathrm{d}x =0

enjoy!

With x i = 1 x_i = 1 , can you explain how i = 1 6 x i = 21 \sum_{i=1} ^ 6 x_i = 21 , as opposed to 6?

Calvin Lin Staff - 5 years, 8 months ago

Log in to reply

Ohhhhhhhhhh my Gooooooo!!!!!!!! How can I do this?

Sorry! I've fixed it.

Sandeep Bhardwaj - 5 years, 8 months ago

Log in to reply

Do you study at resonance kota

Rishabh Deep Singh - 5 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...